Food Safety and Quality Flying Grilled Fish of Produced in Dermasandi Village Tegal - Fatahuddin Fatahuddin; Aef Permadi; Hari Eko Irianto (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Food safety and product quality are very important things applied in the processing of fishery products. This study aims to determine the food safety and quality of flying fish products produced by the village of Dermasandi. Flying fish is a traditional processed product that is very popular with the community because it has a distinctive texture and aroma. The sample of flying grilled fish was tested in the laboratory of the Regional Technical Implementation Unit for Testing and Application of Quality of Fishery Products in Cirebon. The results obtained are sensory test parameters with results 8 - 8.17, moisture content with results 67.51% - 68.11%, fat content with results 0.45% - 1.41%, Total Plate Count (TPC) with a yield of  110,000 – 120,000 kol/g, and Escherichia coli with a yield of ˂ 3 APM/g